PHILOSOPHICAL PARADOXES IN STOPPARD'S THE REAL THING AND JUMPERS: A STUDY OF EXISTENTIAL ABSURDITY AND IDENTITY - Dhanda, Raveendar Reddy; Palwekar, S.D. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Tom Stoppard’s works have long been celebrated for their intricate interplay of intellectual thought and dramatic form. Two of his significant plays, The Real Thing (1982) and Jumpers (1972), engage deeply with existential themes, examining the complexities of human relationships, identity, and the search for meaning in an absurd world. In The Real Thing, Stoppard critiques the notion of “truth” in human interactions, presenting a world where personal integrity and love seem increasingly elusive. Meanwhile, Jumpers explores the collision between existential questions of morality, faith, and intellectual pursuit, dramatizing a world in which traditional values are called into question. This paper examines how both plays reflect existential concerns—identity, freedom, absurdity, and the quest for meaning—while also challenging the boundaries between philosophy, theatre, and the human experience. By analysing the existential dilemmas in The Real Thing and Jumpers, this paper underscores Stoppard’s unique ability to weave philosophical inquiry into the fabric of modern theatre.